Properties of sustainable concrete consisting crushed eggshell waste as fine aggregate replacement - Khairunisa, Muthusamy; Abidatul Munawwarah, Kamaruzaman; Hanis Nadiah, Ruslan; Mohammed A., Ismail (Penerbit UMP, 2023)
The excessive extraction of sand from riverbeds has adverse effects on river ecosystems and aquatic life. Simultaneously, the disposal of eggshells from certain food manufacturing facilities into landfills contributes to pollution. Incorporating crushed eggshells as a partial replacement for sand in concrete can reduce the demand for natural sand, thus decreasing the need for sand mining from rivers. The present research investigates the effect of crushed eggshells as partial sand replacement on workability, compressive strength, and splitting tensile strength of concrete. Five different concrete mixtures were tested, with crushed eggshells replacing sand at percentages ranging from 0% to 20% by weight. All specimens underwent water curing and were subjected to three tests: slump, compressive strength, and splitting tensile strength. The incorporation of eggshells, finer than sand, reduced workability but showed acceptable strength up to a 10% replacement rate. In conclusion, using eggshells as a sand substitute in concrete production can contribute to a cleaner environment and support river ecosystem sustainability.